The Effectiveness Of Using Self-Talk Strategy To Improve Students English Speaking Skill Of The Eleventh Grade Students AT SMKN 1 Bagor In The Academic Year 2021/2022 - Hasna khansa khairunnisa; Hariyono Hariyono (Dharma Pendidikan, 2022)
The objectives of the research are (1) To find out students' achievement in speaking skill before applying Slf-Talk Method. (2) To find out students' achievement in speaking skill after applying Slf Talk Method. (3) To find out the effectiveness before and after being taught using of Self-Talk Method to improving students' speaking skill at the second years of SMKN 1 Bagor in academic year 2021/2022. This research is Pre-Experimental with one group pre-test post-test. The research was done in SMKN 1 Bagor in the academic year of 2021/2022, by using the population whole class XI with the total 461 students, the sample used by the writer is the class XI Tata Boga 1 that consists of 36 students. The technique of sampling is using purposive sampling. The collecting data in this research by using test. The technique of analysis data used to analyze the data in this research is statistical analysis data t-test. Based on the result of the test, students show the score - average pre test 63,9 and post test 81. The category is good. Based on the results of analysis level significance in d.b 5% is 35 value table is 1,690 and value of t-test is 13,2. It can be concluded as follow: ttest > ttable so, Ho is rejected and Ha is accepted. So that, “There is significant effectiveness before and after being taught using of Self-Talk Method to improving students' speaking skill at the second years of SMKN 1 Bagor in academic year 2021/2022.